Effectiveness and safety of atezolizumab, nivolumab and pembrolizumab in metastatic non-small cell lung cancer - Amparo Burgos-San José; Claudia Colomer-Aguilar; Daniel Martínez-Caballero; Bartomeu Massutí-Sureda (Elsevier, 2021)
Objective: To determine the effectiveness and safety of atezolizumab, nivolumab and pembrolizumab in patients with non-small cell lung cancer. Method: This is a retrospective observational study including patients treated in second line and beyond. The effectiveness of treatment was assessed by means of overall survival and progression free survival measurements. Toxicity was described according to the Common Criteria for Adverse Event Terminology v5.0. Results: The study included 8 patients treated with atezolizumab,19 with nivolumab, and 16 with pembrolizumab. Median progression free survival with atezolizumab was 9.6 months (95%CI 2-17.2), 12.6 months (95%CI 6.9- 18.2) for nivolumab, and 8.5 months (95%CI 0-19) for pembrolizumab. Median overall survival was 13.4 months (95%CI 6- 20.9) for nivolumab. Both PFS and OS were statistically higher in patients with grade 0-1 metastasis in the case of nivolumab, and in ECOG 0-1 patients for pembrolizumab. Median overall survival was not reached for atezolizumab or pembrolizumab. Around 85% of patients suffered adverse effects of some degree. Two of the patients treated with nivolumab developed vitiligo. Overall survival of both was higher than 2.5 years. Conclusions: For the patients included in the sample, nivolumab was less effective in those with two or more metastases; the effectiveness of pembrolizumab was lower in ECOG-2 patients. Vitiligo was related to a more durable response to treatment.